A Developmental Perspective in Learning the Mirror-Drawing Task - Julius, Mona Sharon; Adi-Japha, Esther (Frontiers in Human Neuroscience, 2016)
Is there late maturation of skill learning? This notion has been raised to explain an adult advantage in learning a variety of tasks, such as auditory temporal-interval discrimination, locomotion adaptation, and drawing visually-distorted spatial patterns (mirror-drawing). Here, we test this assertion by following the practice of the mirror-drawing task in two 5 min daily sessions separated by a 10 min break, over the course of two days, in 5–6-year-old kindergarten children, 7–8-year-old second-graders, and young adults. In the mirror-drawing task, participants were required to trace a square while looking at their hand only as a reflection in a mirror. Kindergarteners did not show learning of the visual-motor mapping, and on average, did not produce even one full side of a square correctly. Second-graders showed increased online movement control with longer strokes, and robust learning of the visual-motor mapping, resulting in a between-day increase in the number of correctly drawn sides with no loss in accuracy. Overall, kindergarteners and second-graders producing at least one correct polygon-side on Day 1 were more likely to improve their performance between days. Adults showed better performance with greater improvements in the number of correctly drawn sides between- and within-days, and in accuracy between days. It has been suggested that 5-year-olds cannot learn the task due to their inability to detect and encapsulate previously produced accurate movements. Our findings suggest, instead, that these children did not have initial, accurate performance that could be enhanced through training. Recently, it has been shown that in a simple grapho-motor task the three age-groups improved their speed of performance within a session and between-days, while maintaining accuracy scores. Taken together, these data suggest that children's motor skill learning depends on the task’s characteristics and their adopting an efficient performance strategy enabling initial success that can be improved through training.